Phenolic acids from Anisopus mannii modulates phosphofructokinase 1 to improve glycemic control in patients with type 2 diabetes: A double-blind, randomized, clinical trial - Peter U. Amadi; Justice O. Osuoha; Chidi N. Ekweogu; Suha J. Jarad; Esienanwan E. Efiong; Prince C. Odika; Chioma Ejiofor; Oluchi Aloy-Amadi; Govind S. Gill; Chiamaka W. Adumekwe; Ailun Gaowa; Dawei Zhang; et al. (Pharmacological Research)
Phenolic acid-rich fraction from Anisopus mannii (PhAM) contains abundance of ferulic acid, gallic acid, protocatechuic acid, and syringic acid. Among other glycolytic enzymes, in vitro, PhAM counteracted the binding of sodium orthovanadate to phosphofructokinase 1 (PFK-1), improving its activities. In a rat model of diet-induced diabetes, PhAM monotherapy reduced HbA1c by an average of 0.63 % and fasting plasma glucose by 25 mg/dl. This herb rescued β-cells from streptozotocin-mediated destruction, thereby improving glycemic control. Supported by the preclinical trial, eighty-five patients with type 2 diabetes (T2D) receiving first-line medications were enrolled in a double-blind, randomized, placebo-controlled trial with a 90 % power level. Patients were randomized into a placebo group or either of the following two treatment groups: oral administration of 12 mg or 20 mg/kg body weight of PhAM once every 48 h for 6 months. Both treatments were well tolerated. At the endpoint, more than 70 % of patients achieved a 0.5 – 2.0 decrease in HbA1c levels and a > 20 mg/dl decrease in fasting blood glucose, meeting the pre-specified primary outcome. 66 % of patients treated with 20 mg PhAM achieved the < 7 % HbA1c and HOMA-IR of > 1.0 goal. respectively. Our study shows that PhAM can supplement first-line medications to achieve target glycemic control within 6 months.